The Familiarizing of Roby’s Model in Teaching Listening Skill For 8TH Grade Students of Junior High School - Jumbuh Prabowo (International Conference on Education and Language (ICEL), 2013)
Media for teaching listening has various types. One of them is by using software multimedia. As multimedia technology becomes more accessible to teachers and learners of other languages, its potential as a tool to enhance listening skills becomes a practical option. Thus, the writer is interested in familiarizing this software for teaching listening. This software multimedia has been equipped by some features to support teaching listening. Those features are: 1) Free space. This area allows teacher to type or copy dialogues from other sources, 2) F1 to F 12 buttons where each button has difference function. F1 buttons is used to insist on command and sound. F2 and F3 are for choosing the model of speaker and sound. There are seven models of speaker. All the voices of speaker are from British, America, and Australia.  F5 and F6 buttons are used to set time. F7 and F8 are for setting the speed of speaking. F10 is used to listen per sentence and F11 and 12 are used for listen the dialogue per word and letter, 3) Model of saving. There are two types of saving: saving text and saving mp3.The objective of this paper is to familiarize the application of software multimedia for teaching listening.